Determination of polyhexamethyleneguanidine in presence of alkyldimethylbenzylammonium - S. U. Kreyngold; A. N. Kochetov; K. A. Shestakov (Тонкие химические технологии, 2006)
Method for determination of polyhexamethyleneguanidine (PG) in presence of alkyldimethylbenzylammonium (ABA) in disinfection preparations was proposed. The method based on absoption measuring of PG and eosin K ion associate at wave length 555 nm in solutions stabilized by sintanol at pH 9,2